THE SAFETY OF ANTIHYPERTENSIVE AGENTS ON PERIOPERATION OF CARDIAC SURGERY: A SYSTEMATIC REVIEW BASED ON META-ANALYSIS. (April 2021) - Li, Caie; Ma, Liping; Wang, Qiongying; Zhao, Xu; Ma, Ruixin; Li, Ningyin; Yu, Jing
Abstract : Objective: To assess the safety of anti-hypertensive agents including calcium channel blockers (CCBs), angiotensin-converting enzyme inhibitors or angiotensin receptor antagonists (ACEIs/ARBs), and beta blockers during perioperation of cardiac surgery. Design and method: We included randomized controlled trials investigating perioperative application of CCBs, ACEIs/ARBs or beta blockers in cardiac surgery. We extracted data for in-hospital mortality and serious side effects, among which atrial fibrillation (AF), stroke and acute renal failure (ARF) were assessed independently. Results: Twenty-three trials with 5378 patients were included. There were no significant differences between CCBs and placebo, nitroglycerin, or nitroprusside in terms of side effects, AF and ARF. Incidences of side effects (RR [95% CI] 0.55 [0.38, 0.80], I2=0, p < 0.01) and ARF (RR [95% CI] 0.16 [0.05, 0.53], I2=0, p < 0.01) were significantly reduced in ACEIs/ARBs group, compared with placebo, while differences in the incidences of AF and stoke were not found. No differences were found in the incidences of in-hospital death, side effects, ARF and stroke between beta blockers and placebo. However, use of beta blockers significantly reduced the incidence of AF (RR [95% CI] 0.51 [0.39, 0.67], I2=48%, p < 0.01). Conclusions: Perioperative use of CCBs, ACEIs/ARBs or beta blockers does not increase incidences of side effects in patients undergoing cardiac surgery and beta blockers are more appropriate in patients with high risk of postoperative atrial tachycardia. Large randomized trials are needed to confirm these findings.